Germination and Seedling Cold Tolerance in Sorghum: I. Evaluation of Rapid Screening Methods - Tiryaki, Iskender; Andrews, David J. (Agronomy journal, 2001)
Genetic improvement of sorghum [ Sorghum bicolor (L.) Moench] for germination and seedling growth in cold conditions would permit earlier seeding, with a number of benefits. Field evaluation of germination and seedling cold tolerance, while ultimately necessary, is subject to unpredictable weather and limited to one period of the year. The objective of this study was to develop simple and reliable techniques capable of handling large numbers of genotypes, for estimating germination and seedling cold tolerance of sorghum in controlled environment, before field tests, and to compare results with seedling emergence in the field at low soil temperatures. Rate of germination, final germination percentage, and the rate of early shoot growth were evaluated as estimators of cold tolerance using 12 diverse genotypes and their test crosses. The largest difference among genotypes under both normal [25–30°C (day) and 20–25°C (night)] and cold stress conditions (constant 15°C) was shown by the rate of germination in petri dishes and of shoot growth in vertical plexiglass plates in normal conditions only. Rate of germination under controlled cold conditions was strongly correlated ( P < 0.01) with rate of emergence in a field experiment seeded early in cold soil. This work indicated that the use of two tests under controlled conditions, (i) measuring shoot growth rate under normal temperatures followed by (ii) rate of germination at 15°C, and recording data at optimum times will greatly assist in efficiently screening genotypes for cold tolerance before final evaluation in the field.